THE EFFECT OF GREEN LEADERSHIP AND GREEN INNOVATION ON GREEN PERFORMANCE WITH GREEN SELF-EFICACY AS A MEDIATING VARIABLE"AT THE ENVIRONMENTAL SERVICE OF BENER MERIAH DISTRICT" - Tiswanti Ayunasrah; Marbawi; Ibrahim Qamarius; Nur Faliza; Yanita (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of Green Leadership and Green Innovation on employee Green Performance with Self-Efficacy as a mediating variable at the Environmental Service of Bener Meriah Regency, the dependent variables of this study are Green Leadership and Green Innovation for the independent variable is Green Performance, for the intervening variable is Green Self Efficacy. The population in this study were 180 employees at the Bener Meriah Regency Environmental Service. The sampling technique used the census technique and obtained a sample of 180 respondents who were employees at the Bener Meriah Regency Environmental Service. The research method used was the quantitative method, for the data analysis method using Structural Equation Modeling. The results of this study indicate that Green Leadership and Green Innovation have a significant effect on Green Self Efficacy, furthermore Green Leadership and Green Innovation and Green Self Efficacy have a significant effect on Green Performance of employees of the Bener Meriah Regency Environmental Service. This study shows that Green Self Efficacy is the most dominant variable that influences the Green Performance of employees of the Bener Meriah Regency Environmental Service. In this study, Green Leadership and Green Innovation have a significant effect on employee Green Performance through Green Self Efficacy as an intervening variable, it can be concluded that Green Self Efficacy functions as a partial mediation between exogenous and endogenous variables.